2014
DOI: 10.1038/nnano.2014.154
|View full text |Cite|
|
Sign up to set email alerts
|

A carbon nanotube–polymer composite for T-cell therapy

Abstract: Clinical translation of cell therapies requires strategies that can manufacture cells efficiently and economically. One promising way to reproducibly expand T cells for cancer therapy is by attaching the stimuli for T cells onto artificial substrates with high surface area. Here, we show that a carbon nanotube-polymer composite can act as an artificial antigen-presenting cell to efficiently expand the number of T cells isolated from mice. We attach antigens onto bundled carbon nanotubes and combined this compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(157 citation statements)
references
References 44 publications
3
146
0
Order By: Relevance
“…Recently, Fadel et al 112 proposed a CNT-polymer composite that can act as an artificial antigen-presenting cell (APC) to efficiently expand T-cells. Antigens were attached to bundled CNTs, and this CNT complex was combined with polymer NPs containing magnetite and the T-cell growth factor IL-2.…”
mentioning
confidence: 99%
“…Recently, Fadel et al 112 proposed a CNT-polymer composite that can act as an artificial antigen-presenting cell (APC) to efficiently expand T-cells. Antigens were attached to bundled CNTs, and this CNT complex was combined with polymer NPs containing magnetite and the T-cell growth factor IL-2.…”
mentioning
confidence: 99%
“…Fan et al [13] haveconfirmed that intracranial CNT-CpG therapy blocked subcutaneous melanomas. Recently, Fadel et al [14] attached antigens to bundled CNTs (CNTpolymer composite). This CNT complex was conjugated with polymer NPs containing magnetite with T-cell growth factor IL-2.…”
Section: The "Longboat" Anticancer Systemmentioning
confidence: 99%
“…Whereas, PEG-SWCNTs with glucocorticoid-induced TNFR-related receptor GITR ligands were internalized by Treg through receptor-mediated endocytosis and conveyed into the cytoplasm/nucleus cytoplasm and nucleus ex vivo and in vivo [17]. Recently, Fadel et al [14] demonstrated that T-cells suppressed tumor growth. asntigens were combined to bundled CNTs (CNT-polymer composite) and this CNT complex was attached to polymer NPs that contains magnetite and the T-cell growth factor IL-2.…”
Section: T-cell (Treg)-specific Receptorsmentioning
confidence: 99%
“…Finally, a CNT-polymer composite has been designed and used as artificial antigen-presenting cell substrate for expanding T-cells [75]. The stimulation of T-cells against tumor targets is one of the Table 2 Description of the different approaches developed for the capture and separation of cells using magnetic CNMs, and for molecular delivery and extraction and cellular probing using magnetic CNT-based devices.…”
Section: Capture and Separation Of Cellsmentioning
confidence: 99%